Discrimination of Vietnamese species of the genus Rhynocoris (Hemiptera: Heteroptera: Reduviidae) with the utilization of integrative taxonomy - Truong, Xuan Lam; Ha , Ngoc Linh; Truong, Thanh Truc; Nguyen, Dac Dai; Nguyen, Quang Cuong; Eguchi, Katsuyuki (Academia Journal of Biology, 2024)
The genus Rhynocoris Hahn, 1834 is one of the largest genera of the subfamily Harpactorinae. This genus consists of 144 described species widely distributed in the Afrotropical, Palearctic, Sino-Japanese, Oriental, and Nearctic Realms. There are three species, Rhynocoris fuscipes (Fabricius, 1787), Rhynocoris marginellus (Fabricius, 1803), Rhynocoris mendicus (Stål, 1867) recorded in Vietnam. In this study, we attempted to re-examine the Rhynocoris species collected from Vietnam based on external morphology, genital morphology, and COI phylogeny to reveal the species delimitation of this genus in Vietnam. As a result, the independence of the three Rhynocoris species from Vietnam was confirmed. Moreover, R. mendicus was revealed as being a polymorphic species with two intraspecific morphological phenotypes.